Thoracic Society of Australia and New Zealand Position Statement on Acute Oxygen Use in Adults: 'Swimming between the flags'. Issue 4 (17th February 2022) - Barnett, Adrian; Beasley, Richard; Buchan, Catherine; Chien, Jimmy; Farah, Claude S.; King, Gregory; McDonald, Christine F.; Miller, Belinda; Munsif, Maitri; Psirides, Alex; Reid, Lynette; Roberts, Mary; et al.
Abstract: Oxygen is a life‐saving therapy but, when given inappropriately, may also be hazardous. Therefore, in the acute medical setting, oxygen should only be given as treatment for hypoxaemia and requires appropriate prescription, monitoring and review. This update to the Thoracic Society of Australia and New Zealand (TSANZ) guidance on acute oxygen therapy is a brief and practical resource for all healthcare workers involved with administering oxygen therapy to adults in the acute medical setting. It does not apply to intubated or paediatric patients. Recommendations are made in the following six clinical areas: assessment of hypoxaemia (including use of arterial blood gases); prescription of oxygen; peripheral oxygen saturation targets; delivery, including non‐invasive ventilation and humidified high‐flow nasal cannulae; the significance of high oxygen requirements; and acute hypercapnic respiratory failure. There are three sections which provide (1) a brief summary, (2) recommendations in detail with practice points and (3) a detailed explanation of the reasoning and evidence behind the recommendations. It is anticipated that these recommendations will be disseminated widely in structured programmes across Australia and New Zealand.